Association of Multiple Trauma Referral Distance with Mortality in H. Adam Malik General Hospital Medan - Ahmad Akbar Nasution; OK Ilham Abdullah Irsyam; M. Hidayat Siregar (Sumatera Medical Journal, 2023)
Background: The increasing distance from the location of the trauma to the trauma center can cause an increase in mortality. The farther the distance from the trauma center, the higher the mortality of trauma patients. Geographical variations in care may contribute to the effect of the relationship between distance and mortality in trauma patients. Objective: This study wanted to determine the relationship between multiple traumas referral distances and mortality based on ISS at Haji Adam Malik General Hospital Medan. Methods: The study design was an analytic study with the independent variable being the patient's referral distance and the dependent variable being the predictor of mortality in multiple traumas. The approach used in this research design is a retrospective approach. Results: The mean age of the patients was 31.08±17.82 years. Most of the patients were male, most died, and the average referral distance was 79.67 ± 63,244 km. The majority of the ISS scores were 16. The relationship between referral distance and death in the hospital has a P value of < 0.05. Conclusion: There is a significant relationship between multiple trauma patients' referral distance and hospital mortality.